(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2018)
This article analyzes, in a general way, how Brazilian literary criticism of the life and work of José Maria Eça de Queirós (1845–1900) built the identity of the Eça-writer in the twentieth century in Brazil. In this paper, in a specific way, we present a reading that is part of the canon of Queirosian studies in Brazil, titled História Literária de Eça de Queiroz (1939), by Álvaro Lins (1912–1970), verifying how this study became seminal at that time and how it brought some important data about Eça’s biography and work. In addition, we highlight the militant behavior of Álvaro Lins, being featured in the professional literary criticism of the 1930s, and the presence of the impressionistic lineage in the work analyzed. Key words: Eça de Queirós, Álvaro Lins, Brazilian literary criticism, reception, identity.